Processed Bathymetry Grids (NetCDF:GMT format) derived from ship-based Multibeam Sonar Data from Antarctica - Marguerite Bay acquired during the Nathaniel B. Palmer expedition NBP0201 (2002) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a ship-based SeaBeam 2112 Multibeam Sonar system during Nathaniel B. Palmer expedition NBP0201 conducted in 2002 (Chief Scientist: Dr. John Anderson). These data files are of NetCDF Grid format and include gridded Bathymetry data and were processed after data collection. Data were acquired as part of the project(s): Late Pleistocene to Holocene Glacial History of West Antarctica, and funding was provided by NSF grant(s): OPP99-09734.